Dual function of a bee venom serine protease: prophenoloxidase-activating factor in arthropods and fibrin(ogen)olytic enzyme in mammals. - Young Moo Choo; Kwang Sik Lee; Hyung Joo Yoon; Bo Yeon Kim; Mi Ri Sohn; Jong Yul Roh; Yeon Ho Je; Nam Jung Kim; Iksoo Kim; Soo Dong Woo; Hung Dae Sohn; Byung Rae Jin (PLoS ONE, 2010)
Bee venom contains a variety of peptides and enzymes, including serine proteases. While the presence of serine proteases in bee venom has been demonstrated, the role of these proteins in bee venom has not been elucidated. Furthermore, there is currently no information available regarding the melanization response or the fibrin(ogen)olytic activity of bee venom serine protease, and the molecular mechanism of its action remains unknown. Here we show that bee venom serine protease (Bi-VSP) is a multifunctional enzyme. In insects, Bi-VSP acts as an arthropod prophenoloxidase (proPO)-activating factor (PPAF), thereby triggering the phenoloxidase (PO) cascade. Bi-VSP injected through the stinger induces a lethal melanization response in target insects by modulating the innate immune response. In mammals, Bi-VSP acts similarly to snake venom serine protease, which exhibits fibrin(ogen)olytic activity. Bi-VSP activates prothrombin and directly degrades fibrinogen into fibrin degradation products, defining roles for Bi-VSP as a prothrombin activator, a thrombin-like protease, and a plasmin-like protease. These findings provide a novel view of the mechanism of bee venom in which the bee venom serine protease kills target insects via a melanization strategy and exhibits fibrin(ogen)olytic activity.